Che frasi che sono queste?! Alcune strutture esclamative in italiano ed in inglese - Sotkóné Grosz, Anikó (Verbum – Analecta Neolatina, 2013)
In this paper we present a syntactic model aimed at explaining some differences between English and Italian wh-exclamatives. In particular, we will address the question of word order differences and the presence/absence of the finite complementiser in this type of wh-construction. While in English wh-exclamatives exhibit a non-inverted word-order and the obligatory absence of a complementiser, in Italian the verbal predicate generally precedes the subject and the complementiser is optional or obligatory in some cases. Drawing on the insights of recent minimalist studies of subject–auxiliary inversion in English (Branigan 2005; Pesetsky & Torrego 2001; 2007), and of the syntax of exclamatives (Portner & Zanuttini 2003), we will argue for an analysis in which the differences result from the different base position of the subject. We will extend our analysis to shed light on how the structure of wh-questions differs from that of wh-exclamatives, and will explore the special status of these constructions when they contain a subject wh-phrase.